The Future of Representative Democracy - Alonso, Sonia; Keane, John; Merkel, Wolfgang (Cambridge : Cambridge University Press, 2011)
The Future of Representative Democracy poses important questions about representation, representative democracy and their future. Inspired by the last major investigation of the subject by Hanna Pitkin over four decades ago, this ambitious volume fills a major gap in the literature by examining the future of representative forms of democracy in terms of present-day trends and past theories of representative democracy. Aware of the pressing need for clarifying key concepts and institutional trends, the volume aims to break down barriers among disciplines and to establish an interdisciplinary dialogue among scholars. The contributors emphasise that representative democracy and its future is a subject of pressing scholarly concern and public importance. Paying close attention to the unfinished, two-centuries-old relationship between democracy and representation, this book offers a fresh perspective on current problems and dilemmas of representative democracy and the possible future development of new forms of democratic representation.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Representative government and representation; Democracy